2019
DOI: 10.1029/2018gl081666
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing Trend in Black Carbon Aerosols Over the Indian Region

Abstract: We examine long‐term trends in the near‐surface black carbon mass concentration, using multiyear primary data obtained from a dense network (ARFINET) of observatories over the Indian region. We report for the first time the statistically significant decreasing trend in black carbon mass concentration, based on primary data from this region, at an average rate of ~242 ± 53 ng · m−3 · year−1 during the period 2007–2016. This finding contrasts with the generally increasing trend in the columnar aerosol optical de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(35 citation statements)
references
References 45 publications
3
32
0
Order By: Relevance
“…Similarly, contributions of carbonaceous components to the long-term trend of DRF over the Indian region cannot be ignored. From the study of BC trend over the Indian region, Manoj et al (2019) have indicated the presence of carbonaceous aerosols in the elevated lower free-tropospheric regions, even though a general decreasing trend of BC near the surface was revealed from the study. In addition to distinct source processes, influence of regional climate variables (e.g., seasonal and regional rainfall) on the variability of aerosol loading is important.…”
Section: Regional Variability Of Drfmentioning
confidence: 81%
“…Similarly, contributions of carbonaceous components to the long-term trend of DRF over the Indian region cannot be ignored. From the study of BC trend over the Indian region, Manoj et al (2019) have indicated the presence of carbonaceous aerosols in the elevated lower free-tropospheric regions, even though a general decreasing trend of BC near the surface was revealed from the study. In addition to distinct source processes, influence of regional climate variables (e.g., seasonal and regional rainfall) on the variability of aerosol loading is important.…”
Section: Regional Variability Of Drfmentioning
confidence: 81%
“…In India, several recent studies have used satellite and ground based measurements spanning over decade to find the trend in aerosol loading over Indian region 2,2028 . Dey and Girolamo 20 and Dey et al .…”
Section: Introductionmentioning
confidence: 99%
“…The simulated total AOD for natural (dust and sea salt) and anthropogenic aerosols (Figures 10a and 10b) shows that the total AOD is expected to increase in the mitigation scenario relative to the baseline scenario by >0.04 over India, primarily due to larger amounts of anthropogenic sulfate (>10 mg/m). Manoj et al (2019) recently showed decreasing trends in BC but increases in total AOD using a dense network of aerosol observatories established under the Aerosol Radiative Forcing over India (ARFINET). Increasing trends in total AOD over some Indian regions were also reported using ARFINET data earlier by Babu et al (2013).…”
Section: Total Aerosol Effects On the Ism Dynamics Under Anthropogenimentioning
confidence: 99%